Correction: Single-molecule nanopore sensing of actin dynamics and drug binding - Wang,X; Wilkinson,MD; Lin,X; Ren,R; Willison,KR; Ivanov,AP; Baum,J; Edel,JB (Chemical Science, 2020)
Correction for ‘Single-molecule nanopore sensing of actin dynamics and drug binding’ by Xiaoyi Wang et al., Chem. Sci., 2020, 11, 970–979, DOI: 10.1039/C9SC05710B.